1992
DOI: 10.1128/jvi.66.4.2187-2194.1992
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactive and serotype-specific antibodies against foot-and-mouth disease virus generated by different regions of the same synthetic peptide

Abstract: Synthetic peptides based on the VP1 proteins of two serotypes of foot-and-mouth disease virus (FMDV) and having the general formula C-C-(200-213)-P-P-S-(141-158)-P-C-G induce heterologous as well as homologous protection against challenge. Substitution of the sequence consisting of residues 200 to 213 (200-213 sequence) with a second copy of the homologous 141-158 sequence (i.e., homodimers) resulted in failure of either serotype peptide to protect heterologously. The antiviral and antipeptide titers of sera f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Several investigators have reported the ability of selected synthetic peptides to induce neutralizing antibody responses to a limited number of animal viruses (6,7,26,32,34). Unfortunately, in some instances the critical sequences required for antibody induction appear to lie in regions of the virus that are quite variable between different virus isolates and strains, limiting the potential usefulness of these peptides as synthetic antigens or as candidate vaccines (8,20,21,54). Sequence data available for several wild-type and vaccine strains of RV suggest that the region of RV represented by SP15 is well conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported the ability of selected synthetic peptides to induce neutralizing antibody responses to a limited number of animal viruses (6,7,26,32,34). Unfortunately, in some instances the critical sequences required for antibody induction appear to lie in regions of the virus that are quite variable between different virus isolates and strains, limiting the potential usefulness of these peptides as synthetic antigens or as candidate vaccines (8,20,21,54). Sequence data available for several wild-type and vaccine strains of RV suggest that the region of RV represented by SP15 is well conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Linear peptides reproducing this loop from various FMDV serotypes induced nAbs in mice and guinea pigs [ 122 ] and achieved limited protection in swine [ 79 ]. Further work involved chimeric peptides that juxtaposed two antigenic sites, e.g., the G–H loop and the C-terminus of VP1, in linear fashion, also inducing nAbs [ 73 ] and modest protection in swine [ 123 ] and cattle [ 124 , 125 ]. Another linear construction, the ACT peptide, integrated site A (G–H loop of VP1), plus the VP1 C-terminus, plus a T-cell epitope [VP1(21–40)] identified in cattle [ 82 , 86 ], again affording partial protection in a large-scale vaccination trial.…”
Section: Reproducing Fmdv Antigenic Sites By Synthetic Peptidesmentioning
confidence: 99%
“…When sites A and C were joined in the same peptide and used for immunization, the constructs were able to protect cattle against infection [11]. Doel and colleagues [12] synthesized a series of chimeric peptides in which sites A and C originated from either serotype A or serotype O of the virus and they demonstrated that these peptides could protect guinea pigs against infection with both serotypes A and O.…”
Section: Introductionmentioning
confidence: 99%